2017
DOI: 10.1016/j.jff.2016.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic production of protein hydrolysates from steelhead (Oncorhynchus mykiss) skin gelatin as inhibitors of dipeptidyl-peptidase IV and angiotensin-I converting enzyme

Abstract: The objective of this study was to generate protein hydrolysates with dual in vitro inhibitory activities against dipeptidyl-peptidase IV (DPP-IV) and angiotensin-I converting enzyme (ACE), by proteolytic enzymes acting either individually or sequentially on steelhead skin gelatin. The results showed strong dual bioactivity in the low molecular weight (< 3 kDa) fractions obtained by ultrafiltration of hydrolysates produced using the enzymes pepsin, CorolaseN or papain. Alternatively, unfractionated hydrolysate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 33 publications
0
34
0
2
Order By: Relevance
“…As reported in Table , protein hydrolysates (FPE) at a concentration of 5 mg mL −1 exhibited a strong activity against ACE (93.48 ± 0.24%), while the antihypertensive drug, captopril, showed 99.45 ± 0.01% inhibition at all concentration used (1.25 to 5 mg mL −1 ). It is suggested that peptides with ACE‐inhibitory activity are generated during hydrolysis (Cheung & Li‐Chan, ). Inhibition activity was concentration‐dependent as the values increased with increasing hydrolysate concentration from 1.25 to 5 mg mL −1 , with an IC 50 = 0.015 mg mL −1 for FPE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported in Table , protein hydrolysates (FPE) at a concentration of 5 mg mL −1 exhibited a strong activity against ACE (93.48 ± 0.24%), while the antihypertensive drug, captopril, showed 99.45 ± 0.01% inhibition at all concentration used (1.25 to 5 mg mL −1 ). It is suggested that peptides with ACE‐inhibitory activity are generated during hydrolysis (Cheung & Li‐Chan, ). Inhibition activity was concentration‐dependent as the values increased with increasing hydrolysate concentration from 1.25 to 5 mg mL −1 , with an IC 50 = 0.015 mg mL −1 for FPE.…”
Section: Resultsmentioning
confidence: 99%
“…Both ACE and DPP‐IV inhibitory activities are often reported to be associated with lower molecular weight peptides (Iwaniak et al ., ; Power et al ., ). For example, Cheung & Li‐Chan () showed that <3 kDa fractions had better ACE and DPP‐IV inhibitory activities than unfractionated steelhead skin‐gelatin hydrolysates. Based on these findings, the EDUF system used in this study can be a suitable process for delivering fractions containing specific bioactive peptides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrafiltration of steelhead/rainbow hydrolysates yielded fractions of less than 3 kDa with ACE inhibitory activity higher than the activity of the whole hydrolysates (Cheung and Li-Chan 2017). The low MW fractions were prepared from whole hydrolysates using commercial enzyme kits.…”
Section: Antihypertensive Activitymentioning
confidence: 99%
“…Antihyperglycemic activity of fish skin was evaluated using dipeptidyl peptidase IV (DPP-IV) inhibitory assay. Steelhead (Oncorhynchus mykiss) skin gelatin hydrolysates were prepared, and the hydrolysate of 4% papain had the highest DPP-IV inhibitory activity 40-45% (Cheung and Li-Chan 2017). The hydrolysates were purified with ultrafiltration to obtain fraction of less than 3 kDa.…”
Section: Other Biological Activitiesmentioning
confidence: 99%